The organizational culture among nurses at Aceh Mental Hospital - Muhammad Alim Kakani; Ardia Putra; Noraliyatun Jannah; Yuswardi Jannah; Mayanti Mahdarsari (PT WIM Solusi Prima, 2026)
Organizational culture is an important element in creating a conducive work environment, particularly for healthcare professionals such as nurses. In mental hospitals, organizational culture not only reflects individual perceptions, but also shared values, collective behavior, and interaction patterns that influence the quality of healthcare services. This study aimed to describe the organizational culture among nurses at Aceh Mental Hospital. This study used a quantitative descriptive survey design. The sample consisted of 148 inpatient nurses selected using purposive sampling technique. Data were collected using an organizational culture questionnaire developed based on the organizational culture dimensions proposed by Robbins and Judge, including innovation and risk-taking, attention to detail, outcome orientation, people orientation, team orientation, aggressiveness, and stability. The instrument had undergone content validity through expert judgment and construct validity testing, with Cronbach’s Alpha values ≥0.765 indicating good reliability. The results showed that most nurses had a good perception of organizational culture (92.6%). All subvariables were categorized as good, with the highest percentage in stability (92.6%) and the lowest in outcome orientation (86.5%). The findings indicate that organizational culture at Aceh Mental Hospital has generally developed positively and is supported by collaborative work culture, organizational stability, and the characteristics of nurses. However, this study was limited to descriptive analysis and still has the potential for response bias due to self-report measurement.